Green synthesis of MgO nanoparticles and its antibacterial properties - Rotti, Rajeshwari B.; Sunitha, D. V.; Manjunath, Ramya; Roy, Arpita; Mayegowda, Shilpa Borehalli; Gnanaprakash, A. P.; Alghamdi, Saad; Almehmadi, Mazen; Abdulaziz, Osama; Allahyani, Mamdouh; Aljuaid, Abdulelah; Alsaiari, Ahad Amer; et al. (Frontiers in Chemistry, 2023)
Magnesium oxide (MgO) nanostructured particles (NP) were prepared using simple solution combustion technique using leaf extracts of Mangifera indica (Mango - Ma), Azadirachta indica (Neem - Ne) and Carica papaya (Papaya - Pa) as reducing agents. MgO nanostructures synthesized by leaf extracts were calcinated at 5000 C for two hours. To analyze the characteristics of obtained material – Ma-NP, Ne-NP and Pa-NP for dosimetry applications, thermoluminescence (TL) studies were carried out for Co-60 gamma rays irradiated samples in the dose range 10-50 KGy, PaNP and NeNP exhibited well defined glow curve, when compared with MaNP samples. In addition, it was observed that the TL intensity decreases and glow peak temperature shifted towards the higher temperature with the increase in heating rate. The glow peak was segregated using glow curve deconvolution and thermal cleaning method. Kinetic parameters estimated using Chen’s method, trap depth (E) and frequency factor (s) were found to be 0.699, 7.408, 0.4929 and 38.71, 11.008, 10.71for Pa-NP, Ne-NP, Ma-NP respectively. The well resolved glow curve, good linear behavior in the dose range 10 to 50 KGy and less fading was observed in PaNP then compared with MaNP and NeNP. Antibacterial activity was checked against human pathogens Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa. A visible zone of clearance was observed at 200 and 100 µg/mL by the PaNP and NeNP, indicating the death of colonies by the nanoparticles. Therefore, PaNP nanomaterial is a potential phosphor material for dosimetry and antibacterial application compared to NeNP and MaNP.